Evaluation of the dental arch in children with cleft lip and palate by means of 3D digital models - Jorge, Paula Karine (2014)
The aim of this study was to evaluate the dimensional alterations of dental arches of cleft lip and palate children after cheiloplasty at two rehabilitation centers. The sample was composed of 94 digital models and divided in two groups: Group I 23 children, assisted at University of Zurich with presurgical orthopedic intervention (Hotz plate); Group II 24 children, assisted at Hospital for Rehabilitation of Craniofacial Anomalies of the University of São Paulo without presurgical orthopedic intervention. The three dimensional images were used to evaluate before lip repair (stage 1) and approximately 1 year old (stage 2). The obtained measures were: intercanine distance, intertuberosity distance, anterior-posterior arch distance, anterior-posterior cleft length, anterior and posterior cleft width. The comparison between stages 1 and 2 was evaluated in group I, group II and between group I and II. The alterations between groups were verified by Independent t test. If the sample did not present a normal distribution, Wilcoxon and Mann-Whitney tests were used. In Group I, the comparisons between stages 1 and 2 showed that the intertuberosity and anterior-posterior arch distance increased and the intercanine, anterior and posterior cleft distances decreased. In Group II, the comparisons between stages 1 and 2 showed that intertuberosity distance increased and intercanine, anteriorposterior cleft length distances, anterior and posterior cleft widths decreased. The comparison of the dimensional alterations of dental arches between the two rehabilitation centers exhibited differences: in the stage 1, the intercanine distance decreased in Group II; in the stage 2, the anterior cleft width, the intercanine distance and the anterior-posterior cleft length decreased in Group II, suggesting the superposition of maxillary segments; in Group II, there was a greater narrowing of the anterior and posterior cleft widths, suggesting that Hotz plate induced a more evenly and equidistant approximation of maxillary segments in Group I. It is worth emphasizing that more studies should be conduct to reduce the variability in treatment protocols for cleft lip and palate patients, thus assuring the best evidencebased treatment.